Corporate Social Responsibility from Cigarette Industry According to Stakeholder Perspective - Najoan, Hans William; Anandya, Dudi (IPTEK Journal of Proceedings Series, 2020)
This research is aimed to analyze the Corporate Social Responsibility (CSR) activities run given by cigarette industrial companies in Indonesia. Although CSR activity is a form of responsibilities which every company has to do, there are many rules and regulation which limits the scope in cigarette industrial companies can act in. There are four subjects on this research: receiving end of the CSR activity, big three cigarette industry in Indonesia (Sampoerna, Gudang Garam, Djarum), union of cigarette industry that called GAPPRI, people who near with cigarettes. This research uses a qualitative research and interpretivism paradigm in which it focuses on revealing stakeholders point of view on activities that refers to rules and regulations, CSR principles, and strategies which cigarette industrial companies use for CSR activities. There are a lot of perspective in public about CSR activities from cigarette industrial: itâ€™s just a campaign for promote cigarette to children, itâ€™s an activities that built to â€œpretendâ€ theyâ€™re care with others but behind that cigarette industry which causes the problems. Besides every issues, this research found that social responsibility from cigarette industry are pure for serves public, very transparency for every activities, there are no cigaretteâ€™s brand, and not looking for benefit.